2022
DOI: 10.1111/jop.13336
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland polymorphous adenocarcinoma: Clinicopathological features and gene alterations in 36 Japanese patients

Abstract: Background: Polymorphous adenocarcinoma is a common intraoral minor salivary gland carcinoma in Western countries but is extremely rare in Japan. The current study aimed to characterize the clinicopathological features and status of molecular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Interestingly, a sub-group of them demonstrates increased recurrence rates following surgical excision combined or not with a radiation-based therapeutic regimen (27). In contrast, SDCs represent high-grade malignancies characterized by local and distant metastases that appear as rapidly formed neck masses (28) Besides the abovementioned main SGC histotypes, there are also other less frequently observed including clear-cell carcinoma (CCC), basal cell adenocarcinoma (BCAD), acinic-cell carcinoma (ACC), cystadenocarcinoma (CADC), polymorphous adenocarcinoma (PADC), sebaceous adenocarcinoma (SADC), secretory carcinoma (CEC), mucinous adenocarcinoma (MADC), and sebaceous lymphadenocarcinoma (SLADC) (29). Furthermore, more ''exotic' and rare with increased biological aggressiveness carcinoma sub-types include epithelial-myoepithelial carcinoma (EMC), carcinoma ex pleomorphic adenoma (CexPAD), intra-ductal carcinoma (INDC), carcinosarcoma (CSC), squamous cell carcinoma (SCC), anaplastic small cell carcinoma (ASCC), and finally undifferentiated carcinomas (UNC) (30).…”
Section: Sgcs: Histo-genetic Subtypesmentioning
confidence: 99%
“…Interestingly, a sub-group of them demonstrates increased recurrence rates following surgical excision combined or not with a radiation-based therapeutic regimen (27). In contrast, SDCs represent high-grade malignancies characterized by local and distant metastases that appear as rapidly formed neck masses (28) Besides the abovementioned main SGC histotypes, there are also other less frequently observed including clear-cell carcinoma (CCC), basal cell adenocarcinoma (BCAD), acinic-cell carcinoma (ACC), cystadenocarcinoma (CADC), polymorphous adenocarcinoma (PADC), sebaceous adenocarcinoma (SADC), secretory carcinoma (CEC), mucinous adenocarcinoma (MADC), and sebaceous lymphadenocarcinoma (SLADC) (29). Furthermore, more ''exotic' and rare with increased biological aggressiveness carcinoma sub-types include epithelial-myoepithelial carcinoma (EMC), carcinoma ex pleomorphic adenoma (CexPAD), intra-ductal carcinoma (INDC), carcinosarcoma (CSC), squamous cell carcinoma (SCC), anaplastic small cell carcinoma (ASCC), and finally undifferentiated carcinomas (UNC) (30).…”
Section: Sgcs: Histo-genetic Subtypesmentioning
confidence: 99%
“…Some cytogenetic analyses have reported that SDC is characterized by gene alterations on chromosome 17, adenoid cystic carcinoma demonstrates alterations in chromosomes 6, 8, and X, whereas chromosomes 9, 11, 15, and 19 are implicated in the onset and development of MEC (13,14). Furthermore, in basal cell carcinoma, genes on chromosome 16 are deregulated, carcinoma ex pleomorphic adenoma demonstrates chromosome 8 and 12 imbalances, whereas the genetic profile of polymorphous adenocarcinoma comprises alterations in chromosomes 1, 2, 14, 19 and X (15,16). In other rare histopathological entities, such as secretory and clear-cell carcinoma, gene imbalances on chromosomes 12, 15, and 22 have been identified (17).…”
Section: Sgcs: Histopathological Subtypes and Chromosomal Imbalancesmentioning
confidence: 99%